GreenPeace Strategy in Handling Plastic Waste in DKI Jakarta 2017-2020 - Ana Sabhana Azmy; Dinar Amanda (Universitas Medan Area, 2022)
The increase in the amount of plastic waste is a worrying environmental problem, due to the nature of plastic that is difficult to decompose. This article analyzes GreenPeace's strategy for handling plastic waste problems in Jakarta during 2017-2020 and the obstacles that occur in implementing the strategy. The research uses qualitative research methods, data collection comes from primary data through interviews with informants and secondary data through literature studies from various sources. Using the theory of NGO strategy put forward by John McCormick to see the GreenPeace method in solving the problems that occur. The results showed that GreenPeace carried out several strategies in handling plastic waste in Jakarta with a tendency to use five of the nine strategies described by John McCormick, namely the strategy of working with Elected Officials, Bureaucrats, and Employess of corporations by holding activities with the theme of plastic waste, raising and spending money. for campaigns on environmental issues including plastic waste, campaigning and organizing public protests conducted several times with other communities, promoting media coverage of environmental as a tool to expand the issue of plastic waste, exchanging information in the form of workshops and educational activities, undertaking research to produce accurate data, generating local community involvement in environmental protection to increase public awareness. GreenPeace's obstacles in carrying out strategies from the government's external side in addressing existing problems and industrial companies that continue to use single-use plastic without immediately looking for other alternatives. While the internal side is the lack of intensity of GreenPeace in advocating the government.